Fully digital encryption technique - Arizaga, Ricardo (2003)
We propose an alternative fully digital encryption technique based on using the Fourier transform of the original object to be processed and a speckled reference wave as encryption mask. Once encrypted, the Fourier transform spectrum of the object is holographically stored. The original data recovering is performed by digital reconstruction using the same encryption mask, which is also holographically stored. Quality of reconstructed data is evaluated as a function of the sensed encrypted data. Computer simulations and experimental results are presented to demonstrate the method.